MANUAL OF BONE MARROW EXAMINATION. - ISLAM, ANWARUL (CAMBRIDGE SCHOLARS PUBLIS, 2020)
This volume presents a systematic approach to the methods of procurement and examination of bone marrow (aspiration and trephine biopsy) samples that play a crucial role in the diagnosis and management of patients with various hematological, as well as non-hematological, conditions. It systematically explains how to obtain and process bone marrow samples and outlines the methods employed to carry out this specialized clinical procedure safely and effectively.Both aspiration and trephine (core) biopsy techniques are described in detail with the relative merits and illustrations of each highligh.